THE CONTRIBUTION OF HERITAGE FLAGS IN INSTILLING NATIONALIST VALUES IN SCOUT EXTRACURRICULAR ACTIVITIES - Budi Budi; Latifah Zahara; Naila Dewi; Nurul Hasanah (Journal of Educational Science Learning and Research, 2024)
The aim of this research is to identify learning to instill social and religious values ​​for students in Islamic boarding schools. The approach used in this research is a descriptive qualitative approach, observation, interview and documentation methods. The results of this research can be explained.. The results of this research show that (1) contribution heritage flag scout extracurricular activities have experienced developments in terms of facilities and organization such as appointing trainers who have coaching certification, providing materials about nationalism and providing physical training that meets standards. (2) contribution The heritage flag of the scout's extracurricular activities has been proven to have a more disciplined attitude higher than other students, especially in terms of time, Scout members relatively come to school early because they have to do morning assembly. (3) contribution The heritage flag of scout extracurricular activities has a high spirit of nationalism, this proven by member contributions heirloom flag from the activities of scout scouts who have the initiative to wash the flag red and white, when the members heard the national anthem Indonesia Raya Paskibra without being given instructions took the perfect stance. This shows that contribution the heritage flag of scout extracurricular activities can help and form students' disciplinary character and nationalist attitudes.